ANALYSIS OF THE STUDENTS TENDENCY TO CONTINUE TO SENIOR HIGH SCHOOL IN IX GRADE STUDENTS AT SMP N 18 SURAKARTA IN 2019/2020 ACADEMIC YEAR - Ansari, Dimna Anjar; Kusumaningtyas, Lydia Ersta; Koesdyantho, AR (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
This research entitled Analysis of Students' Trends in Continuing Education in Senior High School in Class IX Students of SMP Negeri 18 Surakarta for the 2019/2020 Academic Year was conducted from August to September 2020 at SMP Negeri 18 Surakarta. This study aims to determine how to analyze the tendency of students to continue their education in high school in class IX students of SMP Negeri 18 Surakarta in the academic year 2019/2020